Description of the caring behavior of nurses in nursing services in the surgical room of Santa Elisabeth Hospital Medan in 2022 - Br. Karo, Mestiana; Pane, Jagentar P.; Purba, Iin Gloria (International Journal on Health and Medical Sciences, 2023)
Caring behavior is a person's act of caring for others who are attentive, provide comfort, sensitive, responsible and honest with themselves and others. Caring behavior is very important in nursing actions, a nurse's caring attitude which is based on caring, empathy, sensitivity and responsibility in providing nursing care can increase patient satisfaction, this can affect the quality of nursing services. Therefore, the nurse as someone who cares for the patient must act with care. This study aims to describe the caring behavior of nurses in nursing services in the Surgical Room of Santa Elisabeth Hospital Medan in 2022. This study used a descriptive research design using a convenience sampling technique with a total sample of 41 respondents. The instrument used was the nurse's caring behavior questionnaire. The results showed that the caring behavior of nurses was in the very good category, with a total of 41 respondents (100.0%). Therefore, for nurses to maintain caring behavior for patients.